Tubercular meningitis with altered sensorium in a chronic alcoholic patient: a case report - Krovvidi, Sahithi; Kodali, Venkata Umakanth; Chundu, Umesh Chandra; Naraharasetty, Akhila; Anne, Yochana Sai (International Journal of Research in Medical Sciences, 2025)
A 35-year-old Indian male was referred to Vidhatha hospital, Vijayawada, Andhra Pradesh with history of fever, shortness of breath (Grade III), drowsiness, altered sensorium and generalized weakness for 20 days. The patient is chronic alcoholic and smoker. On examination, patient was disoriented and exhibited neck stiffness. Pleural fluid was positive for Mycobacterium tuberculosis. CT brain indicated vasogenic oedema, and mild hypodense areas in bilateral periventricular regions. MRI brain suggested mild leptomeningeal enhancement in cortical and sub-cortical regions. CSF analysis revealed lymphocytic pleocytosis (100), lowered glucose level (21 mg/dL) and markedly elevated protein level (312.5 mg/dl). Owing to, a diagnosis of tubercular meningitis was established and antitubercular medication with rifampcin, isoniazid, ethambutal, and pyrazinamide, as well as dexamethasone was initiated. Within two days of treatment, he showed signs of improvement, recognised the surroundings and responded to short conversations. The patient was sensitized regarding the adverse effects of smoking and alcoholism and was advised to continue treatment for additional six months.